2011
DOI: 10.1016/j.biomaterials.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic quantitative visualization of single cell alignment and migration and matrix remodeling in 3-D collagen hydrogels under mechanical force

Abstract: We developed a live imaging system enabling dynamic visualization of single cell alignment induced by external mechanical force in a 3-D collagen matrix. The alignment dynamics and migration of smooth muscle cells (SMCs) were studied by time lapse differential interference contrast and /or phase contrast microscopy. Fluorescent and reflection confocal microcopy were used to study the SMC morphology and the microscale collagen matrix remodeling induced by SMCs. A custom developed program was used to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
4
42
0
Order By: Relevance
“…This finding confirms the observations in the literature showing that smooth muscle cells orient perpendicularly to the direction of maximal stress or stretch [14,15]. However, Pang et al [16] have demonstrated that cells in a 3D environment respond in parallel to the direction of the mechanical force. In addition to the stretch direction, the response of cell reorientation is found to depend on the stretching magnitude as shown in Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding confirms the observations in the literature showing that smooth muscle cells orient perpendicularly to the direction of maximal stress or stretch [14,15]. However, Pang et al [16] have demonstrated that cells in a 3D environment respond in parallel to the direction of the mechanical force. In addition to the stretch direction, the response of cell reorientation is found to depend on the stretching magnitude as shown in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…However, most studies in the literature have been mainly focused on growth responses without consideration of contractility, whereas some studies just pay attention to the change of cell contractile phenotype or alteration of contraction marker such as SM-α-actin and myosin heavy chain [12,[15][16][17][18][19][20][21][22]. Although contraction phenotype and marker can be considered as a parameter for the contractility function of cells in a certain extent, the direct effects of stretch on cell contraction have barely been investigated.…”
Section: Discussionmentioning
confidence: 97%
“…Recent reports show that the mechanical properties of the extracellular matrix (ECM) alter VSMC migration and gene expression [43 -45], suggesting that the mechanical properties of the substrate matrix should be taken into account. As reported in a single cell three-dimensional culture under mechanical stimulation, single cell alignment and migration were dynamically and quantitatively visualized in three-dimensional collagen hydrogels under mechanical force [46].…”
Section: Haemodynamic Factors and Vascular Smoothmentioning
confidence: 84%
“…Figure 1e appears as only one line because the alignment vector length (green) is exactly equal to the orientational order parameter (blue), meaning that the alignment vector is the accurate measurement of fiber alignment as the orientational order parameter did. Additionally, the alignment vector offers the direction of fiber alignment that other alignment measurements15202122 could not. Figure 1f shows the alignment vector angle for the simulated fibers in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Collagen is a major component of the ECM; methods for automated extraction of collagen fiber segments and quantifying fiber alignment have been developed171819. In addition, several measures, including the orientational order parameter15, alignment coefficient20, and alignment index2122 have been developed to quantify fiber alignment. These measures are based on the fiber angular distribution, where the fiber alignment is 0 if all fibers are randomly distributed, and 1 if all fibers are perfectly aligned.…”
mentioning
confidence: 99%